Central banks' responses to the Covid-19 pandemic: The case of the Bank of Central African States - Simplice Asongu; Nathanael Ojong; Valentine B. Soumtang (African Governance and Development Institute (AGDI), 2021)
This study explores the responses to the COVID-19 pandemic by the Bank of Central African States (BEAC), which is the central bank for countries in the Central African Economic and Monetary Community (CEMAC), that is, Cameroon, Chad, Gabon, Equatorial Guinea, Central African Republic, and the Republic of Congo. While hitherto, BEAC had fundamentally focused on fighting inflation and promoting monetary integration and financial stability in its member states, the COVID-19 pandemic, among other factors, has motivated it to also shift its policies towards targeted credit programmes and more economic growth. This study sheds light on four core aspects: (i) the socio-economic context of the CEMAC region prior to the COVID-19 pandemic, (ii) BEAC as a lender of last resort, (iii) historical, contemporary, and future insights surrounding targeted credit programmes, and (iv), suggestions for the path forward in terms of reforms, with emphasis on inclusive growth and monitoring economic development at the regional level.
Keywords: 330; Covid-19 pandemic; monetary policy; central bank responses; CEMAC; BEAC